Immunogenicity of the tuberculosis vaccine MVA85A is reduced by coadministration with EPI vaccines in a randomized controlled trial in Gambian infants. - Ota, M; Odutola, A; Owiafe, P; Donkor, S; Owolabi, O; Brittain, N; Williams, N; Rowland-Jones, S; Hill, A; Adegbola, R; McShane, H (2011)
New tuberculosis vaccines are urgently needed to curtail the current epidemic. MVA85A is a subunit vaccine that could enhance immunity from BCG vaccination. To determine MVA85A safety and immunogenicity as well as interactions with other routine vaccines administered in infancy, we randomized healthy 4-month-old infants who had received Bacille Calmette-Guérin at birth to receive Expanded Program on Immunization (EPI) vaccines alone, EPI and MVA85A simultaneously, or MVA85A alone. Adverse events were monitored throughout. Blood samples obtained before vaccination and at 1, 4, and 20 weeks after vaccination were used to assess safety and immunogenicity. The safety profile of both low and standard doses was comparable, but the standard dose was more immunogenic and therefore was selected for the second stage of the study. In total, 72 (first stage) and 142 (second stage) infants were enrolled. MVA85A was safe and well tolerated and induced a potent cellular immune response. Coadministration of MVA85A with EPI vaccines was associated with a significant reduction in MVA85A immunogenicity, but did not affect humoral responses to the EPI vaccines. These results provide important information regarding timing of immunizations, which is required for the design of infant efficacy trials with MVA85A, and suggest that modifications to the standard EPI schedule may be required to incorporate a new generation of T cell-inducing vaccines.